EXPLORING DIGITAL DISTRUST AND E-PAYMENT ADOPTION AMONG RURAL ADULTS IN CROSS RIVER STATE, NIGERIA: IMPLICATIONS FOR THE ADVANCEMENT OF FINTECH DEVELOPMENT (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the interplay between digital distrust and the adoption of electronic payment (e-payment) systems among rural adults in Cross River State, Nigeria, and its implications for fintech development. Utilizing a mixed-methods approach, data were collected from 200 rural adults through surveys and interviews to assess perceptions of trust, security, ease of use, and social influence on e-payment adoption. Findings reveal that high levels of digital distrust, driven by concerns over security (M = 3.8, SD = 0.9) and privacy (M = 3.6, SD = 1.0), significantly hinder e-payment adoption (β = -0.45, p < 0.01). Demographic analysis indicates that younger adults (18–30 years, 60%) and those with higher education (tertiary, 45%) exhibit greater trust in e-payments. Qualitative insights highlight cultural and infrastructural barriers, such as unreliable internet (80%) and limited digital literacy (65%). The study aligns with the Technology Acceptance Model, extending it to include trust as a critical factor in rural contexts. Recommendations include targeted digital literacy programs, enhanced cybersecurity measures, and community-based trust-building initiatives to foster e-payment adoption. These findings contribute to fintech development strategies by emphasizing the need to address distrust and infrastructure gaps to promote financial inclusion in rural Nigeria, supporting Sustainable Development Goals 8 and 10.